Commercial sexual exploitation of children in the Western Balkans: Regional vulnerabilities and legal responses - Kristina Amerhauser; Ruggero Scaturro (Journal of Illicit Economies and Development (JIED), 2021)
Commercial sexual exploitation of children (CSEC) is receiving necessary attention around the world, but the phenomenon remains underreported in the Western Balkans. Through the first part of this paper the authors set out to provide an overview of the knowledge base of the risks and vulnerabilities of the Western Balkans to CSEC. They underline that there is a clear need for more quality and quantity of data. Indeed, the lack of awareness of key actors in the child protection system makes the region further vulnerable to CSEC. In the second section of the paper, the authors then provide a brief analysis of the Western Balkans' relevant legal commitments at the international and regional levels, and an overview of how sexual exploitation of children is covered in national law. It concludes that efforts to define and regulate CSEC in compliance with international standards need to be accompanied by a better implementation of such norms, as well as by an efficient allocation of resources aimed at increasing awareness and collaboration among the stakeholders concerned.
Keywords: 330; child sexual abuse material; commercial sexual exploitation of children; human trafficking; legal frameworks; organized crime; Western Balkans